Study of coupling-of-modes for wavelet transform processors using surface acoustic wave devices. (January 2023) - Yang, Baoliang; Gao, Lili; Lu, Wenke
Abstract: To accurately evaluate selected parameters of wavelet transform processors (WTPs) using surface acoustic wave (SAW) devices, a model of WTPs based on coupling-of-modes theory is proposed, and the second-order effects, such as electrode reflection, propagation loss, electrode resistance, acoustoelectric conversion and transducer static capacity, are sufficiently taken into account in the model. The admittance matrix, bandwidth, and insertion loss of WTPs are analyzed by combining the two-port electrical network and coupling-of-modes with the P-matrix based on the wavelet transform processors principle. Wavelet transform processors samples with a piezoelectric substrate of ST-X cut quartz and interdigital transducers (IDTs) material of Al thin film were manufactured with a center frequency of 60.0 MHz and a scale of 0.25 to validate the effect of the model. A comparison of the simulated and measured results found that the relative error of the center frequency was 0.57%, the highest relative error of the bandwidth was 4.51%, and the relative error of the insertion loss was 1.24%. The experimental results show that the model is extremely accurate in effective frequency band, and its application will undoubtedly speed up the process of designing and producing wavelet transform processors while also boosting the utilization of wavelet technology throughout industry.